The Functional Assessment of Chronic Illness Therapy–Fatigue (FACIT-Fatigue) scale in patients with axial spondyloarthritis: psychometric properties and clinically meaningful thresholds for interpretation - David Cella; Christine de la Loge; Fatoumata Fofana; Shien Guo; Alicia Ellis; Carmen Fleurinck; Ute Massow; Maxime Dougados; Victoria Navarro-Compán; Jessica A. Walsh (Journal of Patient-Reported Outcomes, 2024)
Abstract Background Fatigue is an important symptom for most patients with axial spondyloarthritis (axSpA). The FACIT-Fatigue is a 13-item patient-reported outcome (PRO) instrument that has been used in axSpA clinical trials to measure fatigue severity and impact on daily activities. However, the psychometric properties of the FACIT-Fatigue are not fully evaluated across the entire spectrum of axSpA including non-radiographic axSpA (nr-axSpA) and radiographic axSpA (r-axSpA). This study determined: (1) the psychometric properties of the FACIT-Fatigue in nr-axSpA, r-axSpA, and the broad axSpA population and (2) FACIT-Fatigue scores representing meaningful within-patient change (MWPC), meaningful between-group differences, and cross-sectional severity bands. Methods Data from two Phase 3 trials in adults with nr-axSpA (BE MOBILE 1; N = 254) and r-axSpA (BE MOBILE 2; N = 332) were analyzed pooled and separately to assess the psychometric properties of the FACIT-Fatigue. MWPC and meaningful between-group difference estimates were derived using anchor-based and distribution-based methods. Cross-sectional fatigue severity bands were estimated using logistic regression analysis. Results The FACIT-Fatigue presented good internal consistency, adequate convergent and known-groups validity, and was sensitive to change over time across the full axSpA spectrum. A 5–11-point increase in FACIT-Fatigue score was estimated to represent a MWPC, with an 8-point increase selected as the responder definition. A 2.14–5.34-point difference in FACIT-Fatigue score change over a 16-week period was estimated to represent a small-to-medium meaningful between-group difference. FACIT-Fatigue score severity bands were defined as: none or minimal (>40), mild (>30 to ≤40), moderate (>21 to ≤30), and severe (≤21). Conclusions These findings support the use of the FACIT-Fatigue as a fit-for-purpose measure to assess fatigue-related treatment benefit in axSpA clinical trials. The proposed score estimates and thresholds can guide FACIT-Fatigue score interpretation across the full axSpA spectrum. Trial registration ClinicalTrials.Gov, NCT03928704. Registered 26 April 2019—Retrospectively registered, https://classic.clinicaltrials.gov/ct2/show/NCT03928704 . ClinicalTrials.Gov, NCT03928743. Registered 26 April 2019—Retrospectively registered, https://classic.clinicaltrials.gov/ct2/show/NCT03928743 .